Chapter Per una lettura dell'Epistola XIII di Giovanni Boccaccio - Lombardi, Tommaso (Studi e saggi, 2021)
The contribution proposes an analysis of some stylistic, thematic and intertextual aspects of Giovanni Boccaccio's letter to Francesco Nelli (1363). In particular, through the highlighting of some significant points of contact of the epistle (Epistola XIII) with the enigmatic and probably coeval work of Corbaccio, it tries to open a perspective on a particularly problematic period of Boccaccio's production from the point of view of a text which has been still little explored by the studies.